The redox and DNA-repair activities of Ref-1 are encoded by nonoverlapping domains. - Xanthoudakis, S (1994)
The DNA binding activity of transcription factor AP-1 is regulated in vitro by a posttranslational mechanism involving reduction/oxidation (redox). Redox regulation is mediated by a conserved cysteine residue in the DNA-binding domain of Fos and Jun. Previously, we demonstrated that a DNA repair protein, Ref-1, could stimulate the DNA binding activity of Fos-Jun dimers by reducing this cysteine residue. To examine the relationship between the redox and repair functions of Ref-1, we generated a series of deletion mutants. Analysis of the truncated proteins in vitro revealed that the redox and repair activities are encoded by distinct regions of Ref-1. Sequences in the N-terminal domain of Ref-1 that are not present in functionally related proteins from other organisms are required for the redox activity, whereas the DNA repair activity requires conserved C-terminal sequences. Chemical alkylation or oxidation of cysteine sulfhydryls inhibits the redox activity of Ref-1 without affecting its DNA repair activity. Crosslinking studies suggest that a direct cysteine-mediated interaction occurs between Ref-1 and Jun.